Enzymatic activities and DNA substrate specificity of Mycobacterium tuberculosis DNA helicase XPB. - Seetha V Balasingham (Public Library of Science (PLoS), 2012)
XPB, also known as ERCC3 and RAD25, is a 3' → 5' DNA repair helicase belonging to the superfamily 2 of helicases. XPB is an essential core subunit of the eukaryotic basal transcription factor complex TFIIH. It has two well-established functions: in the context of damaged DNA, XPB facilitates nucleotide excision repair by unwinding double stranded DNA (dsDNA) surrounding a DNA lesion; while in the context of actively transcribing genes, XPB facilitates initiation of RNA polymerase II transcription at gene promoters. Human and other eukaryotic XPB homologs are relatively well characterized compared to conserved homologs found in mycobacteria and archaea. However, more insight into the function of bacterial helicases is central to understanding the mechanism of DNA metabolism and pathogenesis in general. Here, we characterized Mycobacterium tuberculosis XPB (Mtb XPB), a 3'→5' DNA helicase with DNA-dependent ATPase activity. Mtb XPB efficiently catalyzed DNA unwinding in the presence of significant excess of enzyme. The unwinding activity was fueled by ATP or dATP in the presence of Mg(2+)/Mn(2+). Consistent with the 3'→5' polarity of this bacterial XPB helicase, the enzyme required a DNA substrate with a 3' overhang of 15 nucleotides or more. Although Mtb XPB efficiently unwound DNA model substrates with a 3' DNA tail, it was not active on substrates containing a 3' RNA tail. We also found that Mtb XPB efficiently catalyzed ATP-independent annealing of complementary DNA strands. These observations significantly enhance our understanding of the biological roles of Mtb XPB.